A Bacteriophage DNA Mimic Protein Employs a Non-specific Strategy to Inhibit the Bacterial RNA Polymerase - Wang, Zhihao; Wang, Hongliang; Mulvenna, Nancy; Sanz-Hernandez, Maximo; Zhang, Peipei; Li, Yanqing; Ma, Jia; Wang, Yawen; Matthews, Steve; Wigneshweraraj, Sivaramesh; Liu, Bing (Frontiers in Microbiology, 2021)
DNA mimicry by proteins is a strategy that employed by some proteins to occupy the binding sites of the DNA-binding proteins and deny further access to these sites by DNA. Such proteins have been found in bacteriophage, eukaryotic virus, prokaryotic and eukaryotic cells to imitate non-coding functions of DNA. Here, we report another phage protein Gp44 from bacteriophage SPO1 of Bacillus subtilis, employing mimicry as part of unusual strategy to inhibit host RNA polymerase. Consisting of three simple domains, Gp44 contains a DNA binding motif, a flexible DNA mimic domain and a random-coiled domain. Gp44 is able to anchor to host genome and interact bacterial RNA polymerase via the β and β' subunit, resulting in bacterial growth inhibition. Our findings represent a nonspecific strategy that SPO1 phage uses to target different bacterial transcription machinery regardless of the structural variations of RNA polymerases. This feature may have potential applications like generation of genetic engineered phages with Gp44 gene incorporated used in phage therapy to target a range of bacterial hosts.